F162. Lesion-Constrained Electrical Source Imaging (LC-ESI) in epilepsy surgery for tuberous sclerosis complex: A pilot study. (May 2018) - Peters, Jurriaan M.; Chu, Catherine J.; Boom, Merel; Madsen, Joseph; Stone, Scellig S.; Ouaalam, Hakim; Prabhu, Sanjay; Sahin, Mustafa; Warfield, Simon; Hyde, Damon E.
Abstract : Introduction: Tuberous Sclerosis Complex (TSC) is a genetic neurocutaneous disorder associated with multiple dysplastic lesions called tubers. Neurologically, up to 60% of children with TSC have refractory epilepsy, and are at risk for poor neurological outcome. In these patients epilepsy surgery should be explored, the success of which hinges on the identification of the epileptogenic tuber. Electrical source imaging (ESI) models the cerebral origin of scalp EEG data. In TSC, ESI can yield ambiguous results as the distributed source solution is typically constrained to the cortex, whereas the epileptogenic zone is in subcortical tubers. We tested the clinical utility of lesion-constrained electrical source imaging (LC-ESI) in epilepsy surgery in six children with TSC. Methods: LC-ESI is based on a proposed head model in which the source solution is constrained to multiple lesions, rather than to the cortical ribbon. We performed LC-ESI on the ictal and interictal EEG data from the presurgical workup of six patients with TSC. In addition, tubers were expanded in 3 directions to include an 8 mm perituber rim as a potential seizure onset zone. We used a goodness of fit analysis to quantify the ability of individual tubers to approximate the measured EEG data. Tubers were rank-ordered, and color-coded to determine the overlap of the LC-ESI solution maximum with the surgical resection cavity, in the context of surgical outcome. Comparison was made to Low Resolution Brain Electromagnetic Tomography (LORETA). Results: Patients were grouped according to good outcome (Engel Class I or II, n  = 3), and poor outcome (Engel Class III or IV, n  = 3). LORETA predicted the surgical cavity in 1 patient with good outcome (true positive), and had a positive predictive value of 50% and 100% for interictal and ictal data, respectively. Due to a high number of false negatives (source outside of the cavity in patients with a good outcome), the negative predictive value was only 40% and 60% for interictal and ictal data, respectively. LC-ESI identified individual tubers concordant with the resection cavity in 2 (interictal, PPV 66%), and 3 (ictal, PPV 100%) out of 3 patients with a good outcome. Epileptogenic tubers were identified correctly outside of the resection cavity in 2 (interictal, NPV 66%) and 3 (ictal, NPV 100%) out of 3 patients with a poor outcome, where the resection did not include the epileptogenic tubers. There was no difference between solutions constrained to tubers only as compared to those also incorporating a perituber rim. Conclusion: This pilot study supports clinical utility of LC-ESI in the presurgical workup for patients with TSC. Ictal data was more accurate than interictal data in all models. The epileptogenic tuber identified by LC-ESI was concordant with the resection zone in patients with a good surgical outcome, and appropriately discordant in patients with a poor outcome. LC-ESI outperformed conventional LORETA, but further validation is required.